2014
DOI: 10.1517/13543784.2014.947026
|View full text |Cite
|
Sign up to set email alerts
|

Gevokizumab in type 1 diabetes mellitus: extreme remedies for extreme diseases?

Abstract: Despite the very promising characteristics of gevokizumab, important questions remain to be answered. One important question is what to expect from a combination of this agent with insulin and if there is a subset of patients that might respond more favorably to treatment. We also need to know at what stage in the natural history of T1DM could gevokizumab be most efficacious, as well as its potential effects on cardiovascular outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
3
6
0
Order By: Relevance
“…The extent of protection provided by IL-1bAb was associated with the duration of the treatment, demonstrating pronounced protection when IL-1bAb was injected every day during the 15 days of HSD feeding and a weaker effect when IL-1bAb was given during only the first 5 days of HSD feeding. As shown in our previous studies (5)(6)(7)11,14,15) and confirmed in the current study, IL1b is the sole proinflammatory cytokine expressed by macrophages infiltrating the pancreas. An expression of other proinflammatory markers such as the chemokine MCP1 or the cytokines IL-2, IL-6, TNF-a, and IFN-g could not be detected in the infiltrating macrophages.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The extent of protection provided by IL-1bAb was associated with the duration of the treatment, demonstrating pronounced protection when IL-1bAb was injected every day during the 15 days of HSD feeding and a weaker effect when IL-1bAb was given during only the first 5 days of HSD feeding. As shown in our previous studies (5)(6)(7)11,14,15) and confirmed in the current study, IL1b is the sole proinflammatory cytokine expressed by macrophages infiltrating the pancreas. An expression of other proinflammatory markers such as the chemokine MCP1 or the cytokines IL-2, IL-6, TNF-a, and IFN-g could not be detected in the infiltrating macrophages.…”
Section: Discussionsupporting
confidence: 90%
“…In conclusion, our study supports the concept that inflammation in close vicinity to islets may have a detrimental effect on the ability of b-cells to secret insulin in response to glucose stimulation (14,15). Moreover, it illustrates the complexity of the interrelationships between inflammation, b-cell dysfunction, and diabetes development and supports the notion that preventing pancreatic inflammation is important to preserve b-cell function and avoid diabetes development.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations